(3JdNjU GdfRgI GdeHgLI aj JTMjP GdCPgGf hJYOjd GdCeRLIs - (3OGhO Hf YeQ GdHUjQ GdCfWGcj, J (B1008 (3g` s ((3eMeO Qajb Hf jhfS CafOj GdYeQi s)
(3ChdgG (B:s
(3CeG HYO agPg QSGdI GdfRgI ai GdWH dOGhO GdMcje QMeg Gddg GdHGH GdSGOS ai GdCeQGV GdHGWfI GdNGUI HYVh YVh ef GdQCS Edi GdbOe s
(3BNQgG (B:s
(3gPG BNQ eG CQOfG JdNjUg ef GdfRgI GdeHgLI ai JTMjP GdBPGf hJYOjd GdCeRLI hef CQGO RjGOI aYdjg HJPcQJfG , abO HSWfG ajgG GdcdGe Ydi GdWH heGjJYdb Hg ef GdYdhe s
(3HChdgG agQS HehVhYGJ GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B69 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs